2012
DOI: 10.1063/1.3679153
|View full text |Cite
|
Sign up to set email alerts
|

Multi-step ion beam etching of sub-30 nm magnetic tunnel junctions for reducing leakage and MgO barrier damage

Abstract: Articles you may be interested inMagnetic tunnel junction based out-of-plane field sensor with perpendicular magnetic anisotropy in reference layer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Although the redeposition layer was useful for the side protection of the NER, it must be removed since it may render the MgO tunnel barrier useless by creating a short between the pinned layer and the free layer. This suggested that a multistep ion beam etching, 14 repeating a high angle primary etching step followed by a secondary lower angle etching step, was needed. As shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the redeposition layer was useful for the side protection of the NER, it must be removed since it may render the MgO tunnel barrier useless by creating a short between the pinned layer and the free layer. This suggested that a multistep ion beam etching, 14 repeating a high angle primary etching step followed by a secondary lower angle etching step, was needed. As shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…But it shows after-corrosion and oxidation problems. Ion beam etching (IBE) 14,15 has also been used for magnetic material etching which also has many problems, such as sidewall redeposition, mechanical etch damage, and low selectivity. Despite these problems for MTJ pattering, the deposition and etch back technique employing a hard mask layer to increase selectivity during processing is widely used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p-MTJ layers, deposited by UHV sputtering (ULVAC, Inc.), use TiN(500)/Ta(30)/Ru(100)/Co-Pd multilayer(52) (thicknesses in angstroms) as the bottom electrode and the free layer, CoFeB(11)/MgO(8)/CoFeB (12), as the (001)oriented MgO tunnel barrier layer and CoFeTb(300)/ Ru(100)/Ti(50) as the pinned layer and top electrode. After arrays of 30 nm, dot-pattern, 100 nm thickness hard mask were created by 80 kV electron beam lithography (Nano-Beam, nB3) in NER (propylene glycol monomethyl ether acetate compound); an ion beam etching (IBE) process was performed by tilting the rotating sample stage with a beam supply voltage of 700 V and an acceleration supply voltage of 100 V [18,19]. After IBE, the MTJ pillar dimensions and etching characteristics were measured using a scanning electron microscope (SEM) and a high-resolution transmission electron microscope (HR-TEM).…”
Section: Methodsmentioning
confidence: 99%
“…The etching of metals also has the problem of the redeposition of etching by-products. 12,[188][189][190][191][192][193][194][195][196][197] In self-limiting formation, another difficulty arises for intermetallic compounds or alloys such as CoFe, NiFe, CrFe, and PtMn. Simply, in etching processes for compounds such as high-k materials, dichalcogenides, GaAs, GaP, and GaN, it is difficult to maintain the surface stoichiometry during and after the etching.…”
Section: Future Challengesmentioning
confidence: 99%